Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: IF/log question

  1. Aug 16, 2008 #1
    show that y=x is one solution of the equation (1+x2)y''-2y'+2y=0 and determine a second solution

    im up to the IF which i get as eintegral((2/x0-(2x/1+x2) as does my answer sheet but this when comes out as =(x2)/(1+X2) i am getting confused with how to get here as i would of thought i would i end up with logs but how do i get logs from this with a 2 and a 2x in front? step by step please someone
     
  2. jcsd
  3. Aug 16, 2008 #2

    tiny-tim

    User Avatar
    Science Advisor
    Homework Helper

    eintegral((2/x-(2x/1+x2)

    = e2logx - log(1+x2) + c

    Then use elogy = y. :smile:
     
  4. Aug 17, 2008 #3

    HallsofIvy

    User Avatar
    Science Advisor

    Have you copied the problem correctly? You say that you are to show that y= x is a solution of (1+ x2)y"- 2y'+ 2y= 0 and that is not true: if y= x, then y'= 1 and y"= 0 so the equation becomes (1+ x2)(0)- 2(1)+ 2x which is NOT 0.
     
  5. Aug 17, 2008 #4
    sorry its -2xy' not -2y'
     
  6. Aug 17, 2008 #5
    does e2lnx - ln(1+x2) + c go to 2ln|x/1+x|
     
  7. Aug 17, 2008 #6

    tiny-tim

    User Avatar
    Science Advisor
    Homework Helper

    Nooo …

    that's e2lnx e- ln(1+x2) ec,

    = (elnx)2 e- ln(1+x2) ec :smile:
     
  8. Aug 17, 2008 #7

    HallsofIvy

    User Avatar
    Science Advisor

    Okay, you are given (1+ x2)y"- 2xy'+ 2y= 0 and asked first to show that y= x is a solution and then find another (independent) solution.

    I see no reason to find an integrating factor (which apply to first order equations, not second order, anyway) here- you are not asked to solve the equation "from scratch". If y= x, then y'= 1 and y"= 0 so your equation becomes (1+x2)(0)- 2x(1)+ 2x= 0 which is true. Yes, y= x is a solution.

    Now look for another solution of the form y= xu(x). Then y'= xu'+ u and y"= xu"+ 2u'. Putting that into the equation, (1+ x2)(xu"+ 2u')- 2x(xu'+ u)+ 2xu= (x+ x3)u"+ (2+ 2x2)u'- 2x2u'- 2xu+ 2xu= x(1+x2u"+ 2u'= 0.

    Let v= u' so the equation becomes x(1+x2)v'+ 2v= 0. Then v'= 2v/(x(1+x2)) and that is a separable differential equation.
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook